Role of E-cadherin in the Pathogenesis of Gastroesophageal Reflux Disease - Jovov, Biljana; Que, Jianwen; Tobey, Nelia A; Djukic, Zorka; Hogan, Brigid L M; Orlando, Roy C (The American journal of gastroenterology, 2011)
An early event in the pathogenesis of gastroesophageal reflux disease (GERD) is an acid-induced increase in junctional (paracellular) permeability in esophageal epithelium (EE). The molecular events that account for this change are unknown. E-cadherin is a junctional protein important in barrier function in EE. Therefore, defects in barrier function in EE were sought in GERD as well as whether their presence correlated with abnormalities in e-cadherin. Endoscopic biopsies of EE from GERD (n=20; male 10; female 10; mean age 50 ± 10 years) and subjects with a healthy esophagus (controls; n=23; male 11; female 12; mean age 51 ± 11 years) were evaluated in mini-Ussing chambers and by western blot and immunochemistry; and serum analyzed by enzyme-linked immunosorbent assay (ELISA). A role for e-cadherin was also assessed using a unique conditional knockout of e-cadherin in adult mouse esophagus. EE from GERD patients had lower electrical resistance and higher fluorescein flux than EE from controls; and the findings in GERD associated with cleavage of e-cadherin. Cleavage of e-cadherin in GERD was documented in EE by the presence of a 35-kDa, C-terminal fragment of the molecule on western blot and by an increase in soluble N-terminal fragments of the molecule in serum. Activation of the membrane metalloproteinase, A Disintegrin And Metalloproteinase (ADAM-10), was identified as a likely cause for cleavage of e-cadherin by western blot and immunostaining and a role for e-cadherin in the increased junctional permeability in EE from GERD supported by showing increased permeability after deletion of e-cadherin in mouse EE. The EE in GERD has increased junctional permeability and this is in association with proteolytic cleavage of e-cadherin. As loss of e-cadherin can, alone, account for the increase in junctional permeability, cleavage of e-cadherin likely represents a critical molecular event in the pathogenesis of GERD, and identification of cleaved fragments may, if confirmed in larger studies, be valuable as a biomarker of GERD.